A Liver Cancer Question-Answering System Based on Next-Generation Intelligence and the Large Model Med-PaLM 2 - Qian, Jili; Jin, Zhengyu; Zhang, Quan; Cai, Guoqing; Liu, Beichang (International Journal of Computer Science and Information Technology, 2024)
Chronic diseases are the "number one killer" threatening human life and health. In recent years, the incidence of chronic diseases has been rising, and the trend is younger, and the prevention and control situation is very serious. This study introduces a Liver Cancer Question-Answering System (LCQAS) that leverages next-generation artificial intelligence and the large model Med-PaLM 2 The Med-PaLM 2 medical question answering system, powered by next-generation intelligence and large language models, represents a cutting-edge tool in the healthcare domain. Leveraging advanced artificial intelligence techniques and the capabilities of large language models like Med-PaLM 2, this system aims to provide accurate and comprehensive responses to medical inquiries and queries. With its intuitive interface and contextually relevant answers, LCQAS represents a significant advancement in medical information retrieval for liver cancer management.